Diseño y construcción de un motor Stirling solar tipo alfa de pequeño porte (2018)
This study is about the design and construction of a solar Stirling engine type alpha using as a power source a parabolic disc. This prototype uses air as a working fluid at 1 atm. The development of the project has been carried out in three phases. Initially, the thermodynamic modeling of the motor was carried out by means of first order methods using Matlab in order to analyze theoretically the efficiency and delivered power. Then it is done the movement study in Solidworks to detail in CAD the design of the engine and then select the appropriate materials and manufacturing processes. Finally, the Stirling engine and the solar collector were built for the experimental validation of the efficiency and power reached. The design process was allow to establish the optimum displacement volume that is 78 cm3 with a piston diameter of 5 cm reaching a temperature gradient between the area of compression and expansion of 250°C. Three types of heat source were tested in order to measure the temperatures reached in the expansion and compression zones. They were used as heat sources, the solar dish, a lighter and a blowtorch. The project is part of a group of investigation of thermal systems of the U.A.O which tries to contribute in the solution of the problem of the NIZ (Non-interconnected zones) of the country making use of renewable energy sources by means of alternative systems of generation of electric power